Does Decentralized Decision Making Increase Company Performance Through Its Information Technology Infrastructure Investment? - Amri, Mohamad; Yuserrie, Zainuddin; Alam, Nafis; Kendall, Graham (Elsevier, 2017)
A company's Information Technology (IT) infrastructure is a key factor in its sustainability and ongoing success and profitability. This paper explores the relationship between a company's investment in IT and its performance. Performance is measured, with the help of a Balanced Scorecard (BSC), in four ways; financial, internal business processes, innovation & learning and customer perspective. The relationship between each BSC category serves as indicators of the effect of IT investment on a company's performance. This will help establish the benefits of both financial and non-financial indicators. We focus on the Electrical and Electronic manufacturing performance of companies Malaysia. System Resource Theory (SRT) is used as the background theory to explain the concepts of organizational effectiveness, efficiency, productivity and multidimensional performance measurements and to link the variables used in this study. We conduct an empirical study in order to confirm the moderating effects of decentralized decision making. The results suggest that IT investment produces a significant relationship with all BSC perspectives, but the moderating effect is only significant only from a customer perspective.